Marrying Jonah - Lillard, Amy (Lillard, Amy. Wells Landing., 2017)
Everyone in town knows that Sarah Yoder is enamored with Jonah Miller, even though he's been with his girlfriend, Lorie, for years. But all that changes when Lorie runs off with another man. Inconsolable, his faith in love shattered, Jonah resists everyone's attempts to ease his pain until the unexpected happens.